GERMAN AND UZBEK PHRASEOLOGISMS IN THE CONTEXT OF NATIONAL WORLDVIEW: BASED ON CULTURE AND LINGUISTICS (Scientific journal of the Fergana State University, 2025)
The article analyzes phraseological expressions in the German and Uzbek languages to explore the worldview, cultural peculiarities, and linguistic foundations from a cultural studies perspective. It examines how the phraseological expressions in both languages reflect the worldviews, values, and customs of the people. Phraseologisms are linguistic representations of a nation’s historical experiences, religious, philosophical, and social views. The article discusses the meaning and cultural significance of these phraseological expressions, focusing on the main characteristics of German and Uzbek phraseologies, the layers of meaning they express, and the role of language in the social and cultural context. It highlights the changes and differences in cultural identity, historical experience, and national consciousness. The article also explores the connection between the cultures of Germany and Uzbekistan, the worldview of their peoples, and the relationship between language and phraseology. Moreover, it looks at the role of phraseology in linguistics, its significance in preserving national spirit, and its function in expressing the values of the people.